Exploring the evidence base for national and regional policy interventions to combat resistance. Issue 10015 (16th January 2016) - Dar, Osman A; Hasan, Rumina; Schlundt, Jørgen; Harbarth, Stephan; Caleo, Grazia; Dar, Fazal K; Littmann, Jasper; Rweyemamu, Mark; Buckley, Emmeline J; Shahid, Mohammed; Kock, Richard; Li, Henry Lishi; et al.
Summary: The effectiveness of existing policies to control antimicrobial resistance is not yet fully understood. A strengthened evidence base is needed to inform effective policy interventions across countries with different income levels and the human health and animal sectors. We examine three policy domains—responsible use, surveillance, and infection prevention and control—and consider which will be the most effective at national and regional levels. Many complexities exist in the implementation of such policies across sectors and in varying political and regulatory environments. Therefore, we make recommendations for policy action, calling for comprehensive policy assessments, using standardised frameworks, of cost-effectiveness and generalisability. Such assessments are especially important in low-income and middle-income countries, and in the animal and environmental sectors. We also advocate a One Health approach that will enable the development of sensitive policies, accommodating the needs of each sector involved, and addressing concerns of specific countries and regions.